2020
DOI: 10.1097/md.0000000000022968
|View full text |Cite
|
Sign up to set email alerts
|

Association between abdominal aortic aneurysms and alcohol-related diseases

Abstract: Heterogeneous associations exist between alcohol consumption and the initial presentation of cardiovascular diseases (CVDs). Studies regarding the association between abdominal aortic aneurysms (AAAs) and alcohol consumption are still limited and controversial. We hypothesize that patients with alcohol-related diseases are susceptible to AAA formation due to the presence of overlapping epidemiological factors and molecular mechanisms. We aimed to use a nationwide population-based retrospective cohort study to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Cocaine use has also been identified as associated with development of TAI, potentially because it increases the blood pressure and heart rate, and induces vasoconstriction through synaptic stimulation [20]. This data showed that both high altitude patients, and those with a TAI, had a higher rate of alcoholism than their counterparts which is similar to a study by Ling-Yuan et al which found that there was an increased risk for aortic aneurysms for patients who had underlying alcohol-related diseases [21]. Interestingly while those at a high altitude were more likely to have a normal GCS, having an abnormal GCS significantly increased the odds of having a TAI.…”
Section: Discussionsupporting
confidence: 83%
“…Cocaine use has also been identified as associated with development of TAI, potentially because it increases the blood pressure and heart rate, and induces vasoconstriction through synaptic stimulation [20]. This data showed that both high altitude patients, and those with a TAI, had a higher rate of alcoholism than their counterparts which is similar to a study by Ling-Yuan et al which found that there was an increased risk for aortic aneurysms for patients who had underlying alcohol-related diseases [21]. Interestingly while those at a high altitude were more likely to have a normal GCS, having an abnormal GCS significantly increased the odds of having a TAI.…”
Section: Discussionsupporting
confidence: 83%
“…All the medical information was aggregated from the claims, and the diagnosis was recorded from the international classification of diseases, 9th revision, clinical modification (ICD-9-CM codes). The details of the NHIRD have been elaborated in previous studies [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%